PELATIHAN TEKNOLOGI ASISTIF BAGI FORUM TUNANETRA DI SURABAYA - Arbi, Riski Prasetya; Beny, Acep Ovel Novari; Pamuji, Pamuji; Wagino, Wagino; Murtadlo, Murtadlo (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Assistive technology training aims to enhance the independence of visually impaired participants in accessing digital technology. This program focused on the use of screen readers (NVDA, JAWS, TalkBack) and community-based applications such as Be My Eyes. Using a pre-test and post-test design, 16 participants were involved. Results indicated an increase in the average score from 11.19 to 12.75 with a significance value of 0.005 and a large effect size. The training proved effective in improving participants’ knowledge, skills, and confidence. A follow-up program with advanced modules is recommended.ABSTRAKPelatihan teknologi asistif bertujuan meningkatkan kemandirian tunanetra Forum Tunanetra Surabaya dalam mengakses teknologi digital. Kegiatan ini berfokus pada penggunaan pembaca layar (NVDA, JAWS, TalkBack) dan aplikasi komunitas seperti Be My Eyes. Dengan desain pre-test dan post-test, pelatihan diikuti 16 peserta. Hasil menunjukkan peningkatan skor rata-rata dari 11,19 menjadi 12,75 dengan signifikansi 0,005 dan effect size besar. Pelatihan terbukti efektif meningkatkan pengetahuan, keterampilan, dan kepercayaan diri peserta. Program lanjutan direkomendasikan untuk memperkuat kemandirian dan inklusi digital.